Autologous stem cell transplant for multiple myeloma: Impact of melphalan dose on the transplant outcome. Issue 2 (28th January 2023) - Kumar, Lalit; Sahoo, Ranjit Kumar; Kumar, Sudhir; Baa, Annie K.; Tansir, Ghazal; Pathak, Neha; Malik, Prabhat S.; Sharma, Om Dutt; Mathew, Anisha; Jha, Ankit; Gupta, Ritu; Sharma, Atul; et al.
Abstract: We evaluated impact of melphalan dose on transplant outcomes for multiple myeloma. Between 1995 and 2019 459 consecutive patients received a transplant; 69(15%) received melphalan ≤150 mg/m2 (Mel 150 cohort) and 390 (85%) melphalan 200 mg/m2 (MEL 200 cohort). The primary outcome was overall survival (OS) from the date of transplant. Progression-free survival (PFS), engraftment, transplant response, and cumulative relapse at 2 years were secondary outcome measures. Patients in Mel 150 cohort had adverse clinical and laboratory parameters at base line. Transplant response was better for Mel 200 cohort ( p < 0.024). Median OS at a median follow-up of 88 months was similar in the two cohorts; 100 Vs 102 months (Mel 200), p = 0.817. Median PFS (60.0 Vs 53 months, p = 0.746), relapse at two years (32.4% Vs 30.9%, p = 0.745) and grade 3-4 mucositis ( p = 0.823) were similar. Initial treatment prepares patients better for subsequent similar transplant outcomes despite differences in baseline characteristics.